2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6611283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light finger touch to the upper legs on postural sway and muscle activity during quiet standing

Abstract: The purpose of the present study was to investigate the effects of light finger touch (LT) to one's own body on postural sway and ankle muscle activity during quiet standing. In the first part of the present study, 24 healthy men (19 ± 1 years) stood upright with their eyes closed on a pneumatic balance disk under 3 different conditions. In the first condition, the participants kept their hands in loose fists, and contact between the fingers/palms and the legs was avoided. In the second condition, the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…It is greater in the elderly than in young adults [ 26 - 28 ], with eyes closed than with eyes open [ 29 ], and on an unstable surface than on a stable surface [ 30 ]. However, some researcher reported that plantar flexor (soleus) activity was not significantly changed by a light touch during quiet stance [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is greater in the elderly than in young adults [ 26 - 28 ], with eyes closed than with eyes open [ 29 ], and on an unstable surface than on a stable surface [ 30 ]. However, some researcher reported that plantar flexor (soleus) activity was not significantly changed by a light touch during quiet stance [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the bipedal stance, muscle co-activation of the ankle joint increased with age [ 26 , 27 ], and persons with less physical function during postural control tasks showed higher muscle co-activation of the ankle joints [ 27 , 31 ]. Further, Oshita and Yano [ 9 ] reported that although soleus (plantar flexor) activity did not significantly change with a light touch during quiet stance, tibialis anterior (dorsiflexor) activity significantly decreased. Therefore, a light touch during quiet stance might improve postural stability by decreasing co-activation of the ankle muscles, and provide information about the movement of the body segments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations